CHEMICAL COMPOSITION AND SOME FUNCTIONAL PROPERTIES OF FLOUR AND ISOLATED PROTEIN FROM MUNG BEAN SEEDS (Vigna radiate) CULTIVATED IN IRAQ - Abdul Rahman, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this research was to study the chemical composition and functional properties of flour and protein isolate from mung bean by isoelectric precipitation. Moisture, protein, fat, ash, crude fiber and carbohydrate were 5.88%,  24.52%, 1.24%, 3.33%, 5.22% and 59.81%  for flour and 2.48%, 83.70%, 0.24%, 2.48%, 0.52% and 10.58%  for  isolated protein  respectively. The results of functional properties revealed an increase in solubility rates by increasing the pH values of both flour and isolated protein, the mung bean flour showed higher solubility than protein isolate. The foam capacity of flour was higher than that of protein isolate, however foam stability for protein isolate reached 23.53%,  in flour  it decreased to 10%  after 30 minutes.  It was observed that emlusion  formation was good for mung bean flour and isolated protein, while emlusion stability was better for protein isolate. Data of least gelation concentration  showed that the protein isolate  was able to form gel at 6% concentration, in flour it was noted at 8% and the increase of concentration improve gelation capacity for both. Finally mung bean isolate was treated  with Flavourzyme to obtain hydrolysates  at different degree of hydrolysis which were  characterized for its ability to scavenge  free radicals. It was observed that the antioxidant activity increased by increasing the time of hydrolysis, the activity was near to the effectiveness to ascorbic acid as a control after 4 hours. The most functional properties of  protein isolate were good so it could be considered as potential functional food ingredients.